2010
DOI: 10.1016/j.resp.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia decreases E. coli LPS-induced cytokine production and NF-κB activation in alveolar macrophages

Abstract: Reductions in alveolar oxygenation during lung hypoxia/reoxygenation (H/R) injury are common after gram-negative endotoxemia. However, the effects of H/R on endotoxin-stimulated cytokine production by alveolar macrophages are unclear and may depend upon thresholds for hypoxic oxyradical generation in situ. Here TNF-α and IL-β production were determined in rat alveolar macrophages stimulated with E. coli lipopolysaccharide (LPS, serotype O55:B5) while exposed to either normoxia for up to 24 h, to brief normocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Similar results were also seen for the TLR9 agonist CpG (figure 4B). In contrast, hypoxia compromised TLR4 agonist LPS-induced inflammatory cytokine production (figure 4C), which was consistent with previously reported results in macrophages 17. One potential mechanism is that hypoxia might diminish TLR4 expression in RASF, as reported by Ishida et al 18…”
Section: Resultssupporting
confidence: 92%
“…Similar results were also seen for the TLR9 agonist CpG (figure 4B). In contrast, hypoxia compromised TLR4 agonist LPS-induced inflammatory cytokine production (figure 4C), which was consistent with previously reported results in macrophages 17. One potential mechanism is that hypoxia might diminish TLR4 expression in RASF, as reported by Ishida et al 18…”
Section: Resultssupporting
confidence: 92%
“…Cell sensitivity to LPS is likely to be controlled by the modulation of TLR4 biosynthesis or activity through changes in sensitivities to the signals initiated or received by TLR4. It is well confirmed that blocking MD-2 or TLR4/MD-2 by antagonists may help to attenuate the severity of inflammation induced by LPS-activated AMs [10][11][12][13]. Taken together, MD-2 is an interesting and logical target for pharmacological intervention to prevent or attenuate excessive lung inflammation.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, hypoxia increases the production of pro-inflammatory cytokines upon stimulation with the toxins lipopolysaccharide (LPS)- or Phytohaemagglutinin (PHA) in primary human mononuclear cells 14,15 . In contrast, other studies have demonstrated that hypoxia skews the pro-inflammatory character (M1-like) of macrophages towards an anti-inflammatory M2-like phenotype 16,17 . In addition to these contradictory findings, these in vitro studies are difficult to interpret, as the control condition is usually room air, which has a higher PaO 2 compared to physiologic tissue PaO 2 .…”
Section: Immunologic Effects Of Hypoxiamentioning
confidence: 77%